PENGARUH PEMBERDAYAAN USAHA KECIL DAN MENENGAH TERHADAP PEMBANGUNAN EKONOMI MASYARAKAT PESISIR PANTAI KOTA MANADO (SUATU STUDI PADA DINAS KOPERASI DAN UKM KOTA MANADO) - SENDUK, LANDY; PANGKEY, MASJE SILIJA; LALOMA, ALDEN (Sam Ratulangi University, 2018)
Community empowerment aims to improve the economic capacity of the community. One of the sectorsof community empowerment to improve the economic capacity of the community or economic growth of thecommunity is the empowerment of Small and Medium Enterprises. Judging from the potential of existingbusiness coastal city of Manado in improving the economic development of society is very influential with theempowerment of small and medium enterprises. This research uses quantitative research that is trying to answerwhether there is influence and magnitude of influence of variable of empowering small and medium businessto economic development of coastal society of Manado city. The data were carefully compiled, includingquestionnaires in detailed context and in-depth interviews, as well as analysis results. In simple linearregression test it can be seen that constant value (a) equal to 6,375 mean value of constant of economicdevelopment variable is equal to 6,375, while value of empowerment (b / regression coefficient) equal to 0,484.It is clear that the value of regression coefficient (b) is positive sign of 0.484. Y = 6.375 + 0.484X. The magnitudeof determination is 0.568 or 56.8%. Thus, the development of coastal community economy of Manado City56.8% is influenced by Small and Medium Business Empowerment by Manpower Office and ManpowerGovernment of Manado City, another 43.2% is determined by other factors outside the model of simple linearregression equation. The significance value for the empowerment relationship with the economic developmentis 0.000, meaning the significance value is smaller than the value of 0.05 then it can be said that there is arelationship between empowerment with economic development. and Pearson Correlation value is 0.754, itmeans the level of relationship between empowerment and economic development is in the category of 0.600 -0.799 or strong category. Thus, the empowerment of small and medium enterprises coastal city of Manadoaffects the economic development of coastal communities Manado city.Keywords: empowerment, Small Medium Enterprises, community economic development